SISTEM INFORMASI PENGAJUAN CUTI PEGAWAI BERBASIS ANDROID PADA KEMENTERIAN AGAMA KABUPATEN TIMOR TENGAH UTARA - Yayu Ulfaningsi Subagio; Yoseph P.K Kelen; Budiman Baso (Journal of Informatics and Computing (RANDOM), 2023)
The Indonesian Ministry of Religion, North Central Timor Regency is the Indonesian government ministry in charge of religious affairs. One of the things that employees of the North Central Timor Regency Ministry of Religion office often complain about is that the leave application system is still conventional, namely using a leave application form. With this conventional method, applying for leave is less effective in the work process and takes a long time. To overcome this problem, the right solution is to build an Android-based employee leave application information system application at the Ministry of Religion of North Central Timor Regency. The programming language used in this research is PHP and framework_laravel and the database used in building the SICUTI application is Mysql, the system development method uses the Mobile-D method. The tests used to test the capabilities of the SICUTI application are carried out in two ways, namely software testing using a black box and user testing by distributing questionnaires to 20 respondents who have used the SICUTI application. From the results of the user testing, the SICUTI application has reached the predetermined criteria, namely with a value of 87.67%, which means the SICUTI application is declared good for use.